STRATEGI PENGEMBANGAN USAHA HAYDEI KITCHEN - Diana Kusumahati; Reza Widhar Pahlevi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Snacks are liked by people from all walks of life because they are practical, can be consumed immediately, and have many different flavors and shapes. Snack foods are experiencing rapid development both in terms of type, taste and packaging. Haydei Kitchen itself is a culinary brand that creates culinary products in the form of various cakes and snacks, which will be offered to the wider market. The purpose of writing this final assignment is to determine Haydei Kitchen's business development strategy by first analyzing or determining the company's performance. The research results show that the techniques used to develop the Haydei Kitchen business in the marketing sector are: product strategy, price strategy, place strategy, and promotion strategy. In the operational and production fields, namely raw material strategies, equipment, production methods and finance. In the field of human resources, namely job descriptions, payroll systems, recruitment processes, evaluations and termination of employment relations. In addition, Haydei Kitchen uses the Business Model Canvas to assist in understanding and assessing the overall business plan and its components as well as visually representing strategies in an effort to develop Haydei Kitchen's business.